Предмет: Алгебра,
автор: Решала1337
5.121 Докажите равенство
(a+b)^2-4ab=(a-b)^2
(a-b)^2+4ab=(a+b)^2
Ответы
Автор ответа:
13
1) (a+b)^2-4ab=(a-b)^2
a² + 2ab + b² - 4ab = a² - 2ab + b²
a² - 2ab + b² = a² - 2ab + b²
2) (a-b)^2+4ab=(a+b)^2
a² - 2ab + b² + 4ab = a² + 2ab + b²
a² + 2ab + b² = a² + 2ab + b²
a² + 2ab + b² - 4ab = a² - 2ab + b²
a² - 2ab + b² = a² - 2ab + b²
2) (a-b)^2+4ab=(a+b)^2
a² - 2ab + b² + 4ab = a² + 2ab + b²
a² + 2ab + b² = a² + 2ab + b²
DenisVolk01:
Просто разложить на множители и сложить
Автор ответа:
6
Надеюсь почерк понятен
Приложения:
Похожие вопросы
Предмет: Математика,
автор: terryok4
Предмет: Немецкий язык,
автор: shevchenkoasya02
Предмет: Геометрия,
автор: sashaokhlopkov45g
Предмет: Математика,
автор: voronovvladisl